Resistance training - the next level - Marshall, J.; Brandon, R.; Shepherd, J.; Gamble, P.; Hamilton, A.; Mallac, C. (Peak Performance, 2006)
Strength Training Variety: This introductory chapter looks at how simple changes can improve general gym sessions. (James Marshall) Plyometrics: We know it is effective for lower body strength, but how much can it improve the upper body? (Raphael Brandon) Power Combination: This chapter looks at the potentiation effect, how one training mode can enhance another. (John Shepherd) Endurance: How strength and plyometric training can boost endurance running performance. (Raphael Brandon) Triathlon: A complete strength and conditioning programme for the swimming, cycling and running event. (Raphael Brandon) Women and Young Athletes: A guide to strength training for apprehensive women and youths. (James Marshall and Paul Gamble) Nutrition: High protein-low fat diets and creatine use for strength training are brought into question in two intriguing articles. (Andrew Hamilton) Shoulder injuries: Prehab and rehab guide to the frequent and frustrating injuries that inhibit strength training. (Raphael Brandon and Chris Mallac) Training Guide: A gym-free strength training guide, focused on rehab, but appropriate for everyone looking to stay in top shape. (Raphael Brandon)